Preparation of NIR-sensitive, photothermal and photodynamic multi-functional Mxene nanosheets for laryngeal cancer therapy by regulating mitochondrial apoptosis. (August 2022) - Lin, Yiyi; Xu, Shibo; Zhao, Xingjun; Chang, Linna; Hu, Yanan; Chen, Zhenhua; Mei, Xifan; Chen, Dong
Graphical abstract: Highlights: NIR-sensitive, ROS generating, targeting capable nanoplatforms are attractive in cancer therapy. IR780-modified Ti3 C2 nanosheets were prepared as NIR-triggered nanoplatforms to treat laryngeal cancer through the mitochondrial-dependent apoptosis pathway. The obtained multifunctional materials hold promising potential for laryngeal cancer treatment. Abstract: Laryngeal cancer is the most common malignant tumor for which there is still a lack of effective treatment. Traditional radiotherapy, chemotherapy, and surgery all have significant side effects. Therefore, multifunctional collaborative therapeutic nanoplatforms are attractive to patients with laryngeal cancer. In this study, a near-infrared responsive IR780-modified MXene (Ti3 C2 ) nanosheet was proposed as a strategy for targeted therapy to achieve the synergistic functions of photothermal (PTT) therapy, photodynamic (PDT) therapy and mitochondrial pathway apoptosis. Electron spin resonance results showed that Ti3 C2 @IR780 could produce singlet linear oxygen for PDT. Molecular biology studies showed that Ti3 C2 @IR780 had the outstanding ability to generate ROS to disrupt mitochondrial function, resulting in apoptosis of cancer cells up to 60.51%. In vivo experiments showed that Ti3 C2 @IR780 could effectively aggregate at tumor sites. The temperature of the tumor region could reach 63.7 °C in the presence of near-infrared light. Tumor growth was inhibited by 92% during the treatment, and there was no recurrence. Results of the sections showed an 88.1% reduction in microtumor vascularity with Ti3 C2 @IR780 treatment for 21 days compared to the control group. These findings suggest that this multifunctional nanoplatform with synergistic NIR-sensitive properties can effectively inhibit tumor growth, providing an ideal strategy for cancer treatment.